Gel-type moisture absorbent composition and moisture absorption pack containing the same
Patent Information
- Application Number
- KR1020230140527
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-10-20
- Filing Date
- 2023-10-19
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-10-19
Smart Images

Figure 112023114974083-PAT00001 
Figure 112023114974083-PAT00002 
Figure 112023114974083-PAT00003
Abstract
Description
Technology Field
[0001] The present invention relates to a gel-type hygroscopic composition and a moisture-absorbing pack containing the same. Background Technology
[0002] Generally, moisture-absorbing products are widely used by being placed inside packaging boxes to protect products from moisture during packaging or transportation, and conventionally, they are also widely used in products requiring humidity control, such as automotive lamps and electronic products.
[0003] Silica gel has been widely used as the aforementioned desiccant, but it has the problem of low moisture absorption rate and absorption speed. Accordingly, solidified desiccants containing calcium chloride or magnesium chloride are being researched. However, while these solidified desiccants may have relatively high moisture absorption rates and speeds, they also have the disadvantage of a high release rate of absorbed moisture, making it difficult to maintain a moisture absorption effect for a long period. Accordingly, attempts are made to suppress this release rate by adding modifiers such as structural stabilizers, curing agents, and waxes to the solidified desiccants; however, there is a problem in that it is difficult to suppress the release rate by changing only the composition of the desiccant. The problem to be solved
[0004] The present invention aims to provide a gel-type desiccant composition with improved moisture absorption rate, moisture absorption speed, and release rate in order to improve the problems caused by the high release rate of existing solidified desiccant.
[0005] In addition, the present invention aims to provide a gel-type hygroscopic composition that has excellent moisture absorption and release efficiency while simultaneously reducing costs.
[0006] In addition, the present invention aims to provide a gel-type desiccant composition and a desiccant pack containing the same, wherein the absorption rate, absorption speed, and release rate are all improved by using a multi-layered packaging material for the packaging of the desiccant pack containing the gel-type desiccant. means of solving the problem
[0007] The present invention may provide a hygroscopic composition comprising at least one or two hygroscopic materials selected from the group consisting of magnesium chloride and sodium carbonate; a hygroscopic polymer; and starch.
[0008] According to one embodiment of the present invention, the hygroscopic composition may gel when it absorbs moisture.
[0009] According to one embodiment of the present invention, the hygroscopic composition may comprise 1 to 80 parts by weight of the hygroscopic polymer and 1 to 80 parts by weight of the starch, based on 100 parts by weight of the hygroscopic material.
[0010] According to one embodiment of the present invention, the hygroscopic composition may comprise a polyacrylamide-metal methacrylate salt.
[0011] According to one aspect of the present invention, the starch may comprise starch, modified starch, or a mixture of the starch and the modified starch, and in particular may comprise phosphate-modified starch.
[0012] According to one aspect of the present invention, the hygroscopic composition may further include an additive.
[0013] According to one embodiment of the present invention, the hygroscopic composition may have a moisture absorption rate of 150% or more at 50°C and 95% relative humidity.
[0014] According to one embodiment of the present invention, the moisture absorbent composition may have a moisture absorption rate of 2% / 2hr or more at 50°C and 95% relative humidity.
[0015] According to one embodiment of the present invention, the moisture absorbent composition may have a percentage of the amount of moisture absorbed for 14 days at 50°C and 95% relative humidity at 80°C and 30% relative humidity for 24 hours (hr) of 60% or less.
[0016] According to one aspect of the present invention, a moisture-absorbing pack may be provided, comprising the above-mentioned moisture absorbent composition and a packaging material for a moisture absorbent containing the above-mentioned moisture absorbent composition.
[0017] According to one embodiment of the present invention, the packaging material for a desiccant comprises a polyester nonwoven fabric layer, a polyolefin breathable layer, and a polyolefin-based perforated film layer, wherein each layer further comprises a polyurethane-based adhesive layer, and the polyolefin-based perforated film has a plurality of perforations, the gley permeability of the packaging material for a desiccant is 100 to 3,000 seconds, and the moisture permeability of the packaging material for a desiccant is 500 to 5,000 g / m² 2 · It could be 24 hours.
[0018] According to one aspect of the present invention, the polyurethane adhesive may be a polyurethane adhesive derived from a polyester-based polyol and a polyether-based polyol.
[0019] According to one aspect of the present invention, the polyolefin-based perforated film has 1 to 500 holes / cm 2 It may be a polyolefin-based perforated film in which perforations are formed.
[0020] According to one embodiment of the present invention, the moisture-absorbing pack may have an absorption rate of 250% or more at 50°C and 95% relative humidity.
[0021] According to one embodiment of the present invention, the moisture-absorbing pack may have a moisture absorption rate of 5% / 2hr or more at 50℃ and 95% relative humidity.
[0022] According to one embodiment of the present invention, the moisture-absorbing pack may have a percentage of release amount at 80°C, relative humidity 30%, and 24 hours (hr) of moisture absorption amount at 50°C, relative humidity 95%, and 14 days of 20% or less. Effects of the invention
[0023] The gel-type hygroscopic composition of the present invention has the advantage of having a superior moisture absorption rate compared to conventional solidified hygroscopic agents while simultaneously suppressing the release rate.
[0024] In addition, by including the triple plain packaging material of the present invention in the packaging material of the gel-type desiccant composition of the present invention, a low release rate can be maintained even under high temperature and low humidity conditions, which has the advantage of being easy to transport and store for a long period at room temperature, such as automotive lamp desiccant or moisture-sensitive articles. Specific details for implementing the invention
[0025] The present invention will be described in more detail below through specific examples or embodiments, including the attached drawings. However, the following specific examples or embodiments are merely references for the detailed description of the present invention and the present invention is not limited thereto and may be implemented in various forms.
[0026] Furthermore, unless otherwise defined, all technical and scientific terms have the same meaning as generally understood by one of the art to which the present invention pertains. The terms used in the description of the present invention are merely for the purpose of effectively describing specific embodiments and are not intended to limit the present invention.
[0027] Additionally, the singular form used in the specification and the appended claims may be intended to include the plural form unless specifically indicated otherwise in the context.
[0028] Furthermore, when it is stated that a part "includes" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.
[0029] Additionally, the term "and / or" in the present invention means including each of the mentioned items and all combinations of one or more.
[0030] In addition, 'time' in the present invention is the same as 'hr'.
[0031] Conventional solidified desiccants contain hardening agents such as magnesium oxide in absorbent materials such as calcium chloride, and while they have a better absorption rate than silica gel, they have the problem of releasing absorbed moisture again at high temperatures or low humidity.
[0032] The present invention provides a hygroscopic composition comprising at least one hygroscopic material selected from the group consisting of magnesium chloride and sodium carbonate; a hygroscopic polymer; and starch, thereby providing a hygroscopic composition having an excellent moisture absorption rate while simultaneously having a low release rate.
[0033] According to one embodiment of the present invention, the absorbent composition can gel upon absorbing moisture, so there is no tearing of the absorbent pack due to impact, and the gel properties can minimize the release of the absorbed moisture to the outside of the absorbent. In addition, since the absorbent composition of the present invention does not contain hardening inorganic materials such as magnesium oxide that can cause solidification, the release rate of absorbed moisture can be further suppressed compared to a solid form absorbent composition or an absorbent pack containing it.
[0034] In addition, the hygroscopic material may be at least one hygroscopic material selected from the group consisting of magnesium chloride and sodium carbonate, and preferably may be magnesium chloride. By including the magnesium chloride in the hygroscopic composition, the hygroscopic composition may have a more superior absorption rate and absorption speed.
[0035] Specifically, the hygroscopic polymer may comprise one or more hygroscopic polymers selected from polyacrylate metal salts, polyacrylamide-(meth)acrylic acid copolymers, ethylene maleic anhydride copolymers, cellulose-based thickeners including cross-linked carboxymethylcellulose, methylcellulose, ethylcellulose, hydroxyethylcellulose, and hydroxypropylmethylcellulose, polyvinyl alcohol copolymers, and cross-linked polyethylene oxide. Hygroscopic polymers such as cross-linked metal (meth)acrylate salts, cross-linked polyacrylamide-(meth)acrylic acid copolymers, cross-linked ethylene maleic anhydride copolymers, and cross-linked carboxymethylcellulose are preferred, and even more preferably, hygroscopic polymers of cross-linked or non-cross-linked metal salts based on polyacrylamide-(meth)acrylic acid copolymers are most preferred because they gel well and release of absorbed moisture is lower.
[0036] That is, in the case of the above-mentioned hygroscopic composition mixed with polyacrylamide-(meth)acrylate metal salt, starch, and magnesium chloride, it has the advantage of being more strongly gelled when moisture is absorbed, thereby suppressing moisture release.
[0037] In the above polyacrylamide-(meth)acrylate metal salt, the metal may be one or more selected from magnesium, calcium, sodium, potassium, rubidium, and cesium, but is not limited thereto.
[0038] The weight-average molecular weight of the above polyacrylamide-(meth)acrylic acid copolymer may be 10,000 to 20,000,000 g / mol, specifically 100,000 to 10,000,000 g / mol, specifically 1,000,000 or more, 3,000,000 or more, 5,000,000 or more, specifically 3,000,000 to 10,000,000 g / mol, but is not limited thereto.
[0039] The above starch may be ordinary starch or modified starch, and in particular, ionic modified starch is preferred because it provides superior physical properties when combined with the hygroscopic polymer and hygroscopic material. Of course, the above starch may be included as a mixture of ordinary starch and the above modified starch.
[0040] General starch may be one or more selected from tapioca starch, corn starch, potato starch, glyceryl starch, aluminum starch octenyl succinate, and calcium starch octenyl succinate, preferably one or more selected from tapioca starch, corn starch, and potato starch, specifically corn starch, but is not limited thereto.
[0041] In addition, the modified starch may include one or more selected from acid-hydrolyzed starches and acid-treated starches such as acetylated distarch adipate, acetylated distarch phosphate, starch sodium octenyl succinate, distarch phosphate, monoostarch phosphate, phosphated distarch phosphate, starch acetate, and hydroxypropyl distarch phosphate, but is not limited thereto. When the above modified starch is used, it is better to have a superior improvement effect, for example, of 10% or more, in terms of the absorption rate, absorption speed, and release rate intended in the present invention.
[0042] When the above modified starch and starch are mixed and used, the starch and modified starch may be mixed in a ratio of 9:1 to 1:9, preferably 7:3 to 3:7, and preferably 6:4 to 4:6, but are not limited thereto.
[0043] According to one embodiment of the present invention, the hygroscopic composition may comprise 1 to 80 parts by weight of the hygroscopic polymer and 1 to 80 parts by weight of the starch with respect to 100 parts by weight of the hygroscopic material, and specifically, may comprise 1 to 60 parts by weight of the hygroscopic polymer and 1 to 60 parts by weight of the starch.
[0044] As the above-mentioned hygroscopic composition satisfies the above content range, it has the advantage of having a low release rate not only in high-temperature and high-humidity environments but also in low-temperature and high-humidity environments.
[0045] According to one embodiment of the present invention, the hygroscopic composition may further include an additive. The additive may include one or more selected from agar, Arabic gum, carya gum, carob gum, tragacanth gum, guar gum, carrageenan, ester gum, gellan gum, glucomannan (konjac), guar gum, locust bean gum, sodium alginate, tamarind gum, tara gum, and xanthan gum, but is not limited thereto. The additive may be included in an amount of 0.1 to 20 parts by weight per 100 parts by weight of the hygroscopic material, for example, but is not limited thereto, provided that the purpose of the present invention is achieved.
[0046] According to one embodiment of the present invention, the moisture absorbent composition may have an absorption rate of 150% or more at 50°C and 95% relative humidity, specifically 160% or more, specifically 180% or more, specifically 200% or more, specifically 250% or more, specifically 300% or more, specifically 250 to 320%, but is not limited thereto.
[0047] According to one embodiment of the present invention, the moisture absorbent composition may have a percentage of release amount of 60% or less under conditions of 80°C, relative humidity 30%, and 24 hours relative to the amount of moisture absorbed over 14 days at 50°C and relative humidity 95%, specifically 50% or less, and specifically 40% or less, but is not limited thereto.
[0048] According to one aspect of the present invention, a moisture-absorbing pack may be provided, comprising the above-mentioned moisture absorbent composition and a packaging material for a moisture absorbent containing the above-mentioned moisture absorbent composition.
[0049] According to one embodiment of the present invention, the packaging material for a desiccant comprises a polyester nonwoven fabric layer, a polyolefin breathable layer, and a polyolefin-based perforated film layer, wherein the polyolefin-based perforated film has a plurality of perforations, the gley permeability of the packaging material for a desiccant is 100 to 3,000 seconds, and the moisture permeability of the packaging material for a desiccant is 500 to 5,000 g / m² 2 · It may include 24 hours. By using the packaging material for the absorbent in the absorbent pack, the absorbent pack has the advantage of having excellent moisture absorption rate, moisture absorption speed, and release resistance. The above effect is a remarkable effect that is manifested by the combination of a gel-type absorbent composition and the packaging material for the absorbent, and is not easy to achieve with a combination with a conventional solidified absorbent.
[0050] Specifically, the gley permeability (150 ml air volume) of the above-mentioned packaging material for the absorbent may be 100 to 3,000 seconds, specifically 300 to 2,000 seconds, specifically 500 to 1,500 seconds, but is not limited thereto.
[0051] Specifically, the above moisture permeability is 500 to 5,000 g / m² 2 It may be, specifically, 500 to 4,000 g / m² 2 It may be, specifically 500 to 3,000 g / m² 2 It may be, specifically 500 to 2,000 g / m² 2 It may be, specifically 500 to 1,500 g / m² 2 It may be, specifically 600 to 800 g / m² 2 It may be, but is not limited to this.
[0052] As the above-mentioned packaging material for the desiccant satisfies the above-mentioned permeability and moisture permeability, it has the advantage of having excellent moisture absorption rate and absorption speed when additionally combined with the above-mentioned desiccant composition, while simultaneously having excellent anti-release properties.
[0053] The composition of the packaging material for the above-mentioned desiccant is explained in more detail.
[0054] The polyester nonwoven layer of the above-mentioned packaging material for desiccant may comprise a polyester-based nonwoven fabric. The polyester-based nonwoven fabric may be woven from a polyester-based single fiber or a blend of natural fibers or synthetic fibers with polyester fibers, but is not limited thereto. The natural fibers may include cotton, wool, silk, hemp, etc., and the synthetic fibers may include synthetic fibers such as polyamide fibers and polyester fibers, but are not limited thereto. Furthermore, the polyester-based nonwoven fabric may be manufactured by methods such as needle punching, thermal bonding, spun bonding, melt blowing, or spun lacing, but is not limited thereto. Additionally, the polyester-based nonwoven fabric has a basis weight of 10 to 60 g / m² 2 It may be, specifically, 15 to 50 g / m² 2 It may be, specifically, 20 to 40 g / m² 2 It may be, but is not limited thereto. As the above-mentioned packaging material for the desiccant includes a polyester nonwoven fabric satisfying the above basis weight, it may have the effect of further increasing breathability.
[0055] The polyolefin breathable film layer of the above-described packaging material for moisture absorbents may comprise a polyolefin breathable film. The material of the above-described polyolefin breathable film may be low-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene, or polybutylene, but is not limited thereto. Additionally, the above-described polyolefin breathable film may be manufactured by including an inorganic filler in the above-described polyolefin resin. The above-described polyolefin breathable film may be manufactured by adding an inorganic filler to a polyolefin resin to produce an extruded sheet, and then stretching it, but is not limited to the above manufacturing method. The above-described inorganic filler may be one or more selected from the group consisting of calcium carbonate, talc, clay, kaolin, silica, and diatomaceous earth. The average particle size of the above-described inorganic filler may be selected according to the purpose of the invention and is not limited for moisture permeability, breathability, and mechanical strength, but preferably may be 0.5 to 30 μm, but is not limited thereto. The content may be 20 to 40 parts by weight per 100 parts by weight of the polyethylene resin to improve flexural strength, elasticity, and flexibility, but is not limited thereto. The polyolefin breathable film preferably has a basis weight of 10 to 50 g / m² to maintain moisture permeability, water resistance, and air permeability without tearing easily. Additionally, the polyolefin breathable film may have physical properties such as a moisture permeability of 100 to 10,000 g / m²·24hr, an air permeability of 10 to 5,000 sec, and a water pressure resistance of 50 to 100 cm / H2O.
[0056] According to one embodiment of the present invention, the polyurethane-based adhesive may be a polyurethane adhesive derived from a polyester-based polyol and a polyether-based polyol. The polyurethane-based adhesive comprises a polyether polyol, a polyester polyol, an isocyanate-based curing agent, an accelerator, and a solvent, and the polyurethane-based adhesive prepared with the above composition has the effect of excellent breathability, unlike general adhesives.
[0057] In addition, the polyolefin-based perforated film of the above-mentioned packaging material for the desiccant has 1 to 500 holes / cm in the polyolefin-based film. 2 It may be a film having perforations formed therein, specifically 8 to 30 percm 2 It may be a film having perforations formed therein, specifically 10 to 25 percm 2 The film may have perforations formed therein, but is not limited thereto. As the number of perforations in the polyolefin-based perforated film satisfies the above conditions, the absorption rate of the absorbent including the packaging material for the absorbent can be effectively controlled.
[0058] According to one embodiment of the present invention, the polyolefin-based perforated film may have an average diameter of perforations of 0.01 to 2.0 mm, specifically 0.05 to 1.5 mm, specifically 0.1 to 1.0 mm, and specifically 0.3 to 0.5 mm, but is not limited thereto.
[0059] According to one embodiment of the present invention, the polyolefin-based perforated film may have a perforation rate of 0.1 to 50%, specifically 0.3 to 40%, specifically 0.4 to 30%, specifically 0.4 to 20%, specifically 0.5 to 10%, specifically 0.5 to 5%, but is not limited thereto. In this case, the perforation rate refers to the percentage of the total sum of perforated areas relative to a unit area. The perforation rate range is controlled within the average diameter range of the perforations, and the moisture absorption rate can be controlled more effectively depending on the combination thereof.
[0060] By manufacturing an absorbent pack by packaging the above-described absorbent composition with the above-described packaging material, the absorption rate of the absorbent product can be effectively controlled. In addition, since the absorbent product can have excellent durability, the phenomenon of the absorbent being discharged to the outside due to external impact during transportation and storage can be suppressed.
[0061] Specifically, the moisture absorbent pack may have an absorption rate of 200% or more at 50°C and 95% relative humidity, specifically 250% or more, specifically 300% or more, specifically 250 to 400%, specifically 270 to 350%, and specifically 300 to 320%, but is not limited thereto.
[0062] In addition, according to one embodiment of the present invention, the moisture-absorbing pack may have a moisture absorption rate of 3% / 2hr or more at 50°C and 95% relative humidity, specifically 5% / 2hr or more, specifically 5 to 15% / 2hr, specifically 5 to 10% / 2hr, and specifically 5 to 7% / 2hr, but is not limited thereto.
[0063] In addition, according to one embodiment of the present invention, the moisture-absorbing pack may have a percentage of the amount of moisture absorbed at 80°C, relative humidity 30%, and 24 hours with respect to the amount of moisture absorbed at 50°C, relative humidity 95%, and 14 days that is 30% or less, specifically 20% or less, specifically 19% or less, and specifically 0 to 17% or less, but is not limited thereto.
[0064] According to one embodiment of the present invention, the moisture-absorbing pack may absorb moisture up to 100% under conditions of 40°C, 90% relative humidity, 40°C, 90% relative humidity, and then release a percentage of 5% or less under conditions of 80°C, 30% relative humidity, and 2 hr, specifically 4% or less, and specifically 3% or less, but is not limited thereto.
[0066] The present invention will be explained in more detail below based on the following examples and comparative examples. However, the following examples and comparative examples are merely illustrative of the present invention and are not intended to limit the present invention.
[0068] Moisture-absorbing film performance evaluation
[0069] 1. Gulliver transmittance
[0070] The time it takes for 150 ml of air to pass through was measured using a densometer (Gurley densometer, KP-M4350, Gibae E&T).
[0072] 2. Tensile strength
[0073] The above tensile strength is a value measured according to ISO 1924-2.
[0075] Moisture-absorbing Product Performance Evaluation
[0076] 3. Moisture absorption rate
[0077] The above moisture absorption rate was measured using a constant temperature and humidity chamber at a temperature of 50±2 ℃ and a relative humidity of 95±5% after 14 days. The above moisture absorption rate was calculated as shown in Equation 1 below.
[0078] [Equation 1]
[0079]
[0081] 4. Moisture absorption rate
[0082] The moisture absorption rate was measured after exposing the specimen to a temperature of 50±2 ℃ and a relative humidity of 95±5% for 2 hours using a constant temperature and humidity chamber, and the moisture absorption rate was calculated using the following Equation 2.
[0083] [Equation 2]
[0084]
[0086] 5. Emission rate
[0087] The release rate was measured after releasing moisture by exposing specimens, which were fully humidified using a hot air dryer (constant temperature and humidity chamber) at 50±2℃ and 95±5% relative humidity, to a temperature of 80℃ for 2 hours, 24 hours, and 48 hours. The release rate was calculated using the following Equation 3.
[0088] [Equation 3]
[0089]
[0091] <Manufacturing Example 1> Manufacture of triple-blank packaging material
[0092] Polyester spunbond nonwoven fabric (basis weight 30g / m² 2 A polyurethane adhesive was applied to one side of (CAS No. 25038-59-9), and a polypropylene film (CAS No. 9003-07-0) was adhered to the applied adhesive. Subsequently, a polyurethane adhesive (product of Hichem) was applied to the polypropylene film, and an average of 20 pieces / cm² were attached to the applied adhesive. 2A triple-layer plain film was manufactured by bonding a polypropylene perforated film (CAS No. 9003-07-0, cast PP film, thickness 25 μm) having perforations. The above triple-layer plain film was manufactured by a dry lamination process.
[0094] <Manufacture of desiccants>
[0095] <Example 1>
[0096] A desiccant was prepared by uniformly mixing 100 parts by weight of magnesium chloride (Aldrich), 40 parts by weight of polyacrylamide-sodium methacrylate (CAS No. 25085-02-03), and 60 parts by weight of corn starch (Daesang Co.) using a mixer. 25g of the prepared desiccant was placed into the triple-layer plain packaging material of Preparation Example 1 to produce a moisture-absorbing product. The moisture absorption rate, absorption rate, and release rate of the prepared moisture-absorbing product were measured and listed in Table 1 below.
[0098] <Example 2>
[0099] The procedure was carried out in the same manner as Example 1, except that a hygroscopic agent was prepared by uniformly mixing 100 parts by weight of magnesium chloride (Aldrich, purity 94%), 60 parts by weight of polyacrylamide-sodium methacrylate (CAS No. 25085-02-03), and 40 parts by weight of corn starch (Daesang) using a mixer. The moisture absorption rate, absorption rate, and release rate of the prepared hygroscopic product were measured and listed in Tables 1 and 2 below.
[0101] <Example 3>
[0102] The procedure was carried out in the same manner as Example 1, except that a hygroscopic agent was prepared by uniformly mixing 100 parts by weight of magnesium chloride (Aldrich), 75 parts by weight of polyacrylamide-sodium methacrylate (CAS No. 25085-02-03), and 75 parts by weight of corn starch (Daesang) as hygroscopic materials using a mixer. The moisture absorption rate, absorption rate, and release rate of the prepared hygroscopic product were measured and listed in Table 1 below.
[0104] <Example 4>
[0105] A desiccant was prepared by uniformly mixing 100 parts by weight of magnesium chloride (Aldrich, purity 94%), 40 parts by weight of polyacrylamide-sodium methacrylate (CAS No. 25085-02-03), 60 parts by weight of corn starch (Daesang), and 40 parts by weight of magnesium oxide (KONOSHIMA CHEMICAL, STARMAG 50, average particle size 30 μm) using a mixer. 25 g of the prepared desiccant was placed into the triple-layer plain packaging material of Preparation Example 1 to produce a moisture-absorbing product. The moisture absorption rate, absorption rate, and release rate of the prepared moisture-absorbing product were measured and listed in Table 1 below.
[0107] <Example 5>
[0108] A desiccant was prepared by uniformly mixing 100 parts by weight of magnesium chloride (Aldrich), 40 parts by weight of polyacrylamide-sodium methacrylate (CAS No. 25085-02-03), and 60 parts by weight of hydroxypropyl phosphate starch (INGREDION INCORPORATED, USA) as hygroscopic materials using a mixer. 25 g of the prepared desiccant was placed into the triple-layer plain packaging material of Preparation Example 1 to produce a hygroscopic product. The moisture absorption rate, absorption rate, and release rate of the prepared hygroscopic product were measured and listed in Table 1 below.
[0110] <Example 6>
[0111] A desiccant was prepared by uniformly mixing 100 parts by weight of magnesium chloride (Aldrich, 94% purity), 40 parts by weight of polyacrylamide-sodium methacrylate (CAS No. 25085-02-03), 30 parts by weight of corn starch (Daesang), and 30 parts by weight of hydroxypropyl phosphate distarch (INGREDION INCORPORATED, USA) using a mixer. 25g of the prepared desiccant was placed into the triple-layer plain packaging material prepared in Preparation Example 1 to produce a moisture-absorbing product. The moisture absorption rate, absorption rate, and release rate of the prepared moisture-absorbing product were measured and listed in Table 1 below.
[0113] <Example 7>
[0114] A desiccant was prepared by uniformly mixing 100 parts by weight of magnesium chloride (Aldrich, purity 94%), 40 parts by weight of polyacrylamide-sodium methacrylate (CAS No. 25085-02-03), 60 parts by weight of hydroxypropyl phosphate starch (INGREDION INCORPORATED, USA), and 3 parts by weight of xanthan gum (CAS No.: 11138-66-2) using a mixer. 25g of the prepared desiccant was placed into the triple-layer plain packaging material prepared in Preparation Example 1 to produce a moisture-absorbing product. The moisture absorption rate, absorption rate, and release rate of the prepared moisture-absorbing product were measured and listed in Table 1 below.
[0116] <Example 8>
[0117] The procedure was carried out in the same manner, except that EVA-coated Tyvek (fabric provided by Dupont) packaging material was used instead of the triple plain packaging material prepared in Example 1. The moisture absorption rate, moisture absorption rate, and release rate of the moisture-absorbing product prepared above were measured and listed in Table 2 below.
[0119] <Example 9>
[0120] The procedure was carried out in the same manner, except that EVA-coated Tyvek (fabric provided by Dupont) packaging material was used instead of the triple plain packaging material prepared in Example 2. The moisture absorption rate, moisture absorption rate, and release rate of the moisture-absorbing product prepared above were measured and listed in Table 2 below.
[0122] <Example 10>
[0123] A desiccant was prepared by uniformly mixing 100 parts by weight of magnesium chloride (Aldrich), 40 parts by weight of sodium polyacrylate (CAS No. 9003-04-7), and 60 parts by weight of hydroxypropyl phosphate starch (INGREDION INCORPORATED, USA) as hygroscopic materials using a mixer. 25g of the prepared desiccant was placed into the triple-layer plain packaging material of Preparation Example 1 to produce a hygroscopic product. The moisture absorption rate, absorption rate, and release rate of the prepared hygroscopic product were measured and listed in Table 1 below.
[0125] <Comparative Example 1>
[0126] A desiccant was prepared by uniformly mixing 100 parts by weight of magnesium chloride (Aldrich, 94% purity), 50 parts by weight of polyacrylamide-sodium methacrylate (CAS No. 25085-02-03), and 100 parts by weight of magnesium oxide (KONOSHIMA CHEMICAL, STARMAG 50, average particle size 30 μm) as hygroscopic materials using a mixer. 25 g of the prepared desiccant was placed into an EVA-coated Tyvek packaging material (fabric provided by Dupont) to produce a hygroscopic product. The moisture absorption rate, absorption rate, and release rate of the prepared hygroscopic product were measured and listed in Table 1 below.
[0128] <Comparative Example 2>
[0129] A desiccant was prepared by uniformly mixing 100 parts by weight of magnesium chloride (Aldrich, purity 94%), 100 parts by weight of magnesium oxide (KONOSHIMA CHEMICAL, STARMAG 50, average particle size 30 μm), and 50 parts by weight of PE wax using a mixer. 25 g of the prepared desiccant was placed into an EVA-coated Tyvek packaging material (fabric provided by Dupont) to produce a moisture-absorbing product. The moisture absorption rate, absorption rate, and release rate of the prepared moisture-absorbing product were measured and listed in Table 2 below.
[0131] <Comparative Example 3>
[0132] The procedure was carried out in the same manner as in Comparative Example 2, except that a triple-layer plain packaging material was used instead of the EVA-coated Tyvek (fabric provided by Dupont) packaging material. The moisture absorption rate, moisture absorption rate, and release rate of the moisture-absorbing products manufactured above were measured and listed in Table 2 below.
[0134] MgCl2 SAP Starch MgO Xanthan sword PE wax 50℃, 95% RH Moisture absorption rate (% / 2hr) Moisture absorption rate (%) emission rate situation PAPM PA Starch Modified starch 14th 80℃, 30%, 2hr 80℃, 30%,24hr 80℃, 30%,48hr Example 1 100 40 - 60 - - 5.88 304.55 1.33 17.54 32.67 Gel Example 2 100 60 - 40 - - 6.33 301.09 1.24 17.39 33.75 Gel Example 3 100 75 - 75 - - 5.59 262.11 1.38 18.58 36.53 Gel Example 4 100 40 - 60 - 40 6.50 269.1 3.5 25.15 50.52 Gel Example 5 100 40 - - 60 - 6.23 310.12 1.23 17.12 30.01 Gel Example 6 100 40 - 30 30 - 6.9 314.10 1.12 13.56 26.96 Gel Example 7 100 40 - 60 - 3 6.76 313.65 1.26 15.52 29.05 Gel Example 8 100 40 - 60 - - 6.6 310.36 8.56 35.5 48.5 Gel Example 9 100 60 - 40 - - 6.1 306.56 7.32 33.65 47.52 Gel Example 10 100 - 40 - 60 - 7.8 280.21 6.56 25.3 45.65 Gel Comparative Example 1 100 50 - - - 100 12.81 166.88 16.04 65.21 70.21 High-quality Comparative Example 2 100 - - - - 100 50 5.53 145.37 9.86 47.18 49.09 High-quality Comparative Example 3 100 - - - - 100 50 5.61 151.72 10.83 49.53 52.79 High-quality
[0136] Examples 1 to 3 all have a release rate of 20% or less under release rate conditions (80°C, 30%, 24hr) after full humidity at 50°C and 95%, which is lower than Comparative Examples 1 to 3. In the case of Examples 1 and 2, it can be confirmed that while the moisture absorption rate and moisture absorption rate are similar to Examples 8 and 9, the release rate is actually lower. This is a significant effect resulting from the combination of the gelling type desiccant and the triple-layer plain packaging material.
[0138] As described above, the present invention has been explained by specific details, limited embodiments, and drawings; however, this is provided merely to aid in a more comprehensive understanding of the invention, and the invention is not limited to the above embodiments. Those skilled in the art can make various modifications and variations from this description.
[0139] Accordingly, the scope of the present invention is not limited to the described embodiments, and all things equivalent to or having equivalent variations to the claims set forth below, as well as the claims set forth below, shall be considered to fall within the scope of the concept of the present invention.
Claims
Claim 1 A hygroscopic composition comprising at least one or two hygroscopic materials selected from the group consisting of magnesium chloride and sodium carbonate; a hygroscopic polymer; starch; and modified starch, wherein the hygroscopic composition gels when it absorbs moisture, and the hygroscopic polymer is one or more selected from the group consisting of a metal polyacrylate salt, a polyacrylamide-(meth)acrylic acid copolymer, an ethylene maleic anhydride copolymer, a cellulose-based thickener including cross-linked carboxymethylcellulose, methylcellulose, ethylcellulose, hydroxyethylcellulose, and hydroxypropylmethylcellulose, a polyvinyl alcohol copolymer, and a cross-linked polyethylene oxide. Claim 2 delete Claim 3 A hygroscopic composition according to claim 1, wherein the hygroscopic composition comprises 1 to 80 parts by weight of the hygroscopic polymer and 1 to 80 parts by weight of the starch, based on 100 parts by weight of the hygroscopic material. Claim 4 delete Claim 5 A hygroscopic composition according to claim 1, wherein the hygroscopic composition comprises polyacrylamide-(meth)acrylate metal salt. Claim 6 delete Claim 7 A hygroscopic composition according to claim 1, wherein the modified starch is one or more selected from acid-hydrolyzed starch and acid-treated starch, such as acetylated distarch adipate, acetylated distarch phosphate, starch sodium octenyl succinate, distarch phosphate, monoostarch phosphate, phosphated distarch phosphate, starch acetate, and hydroxypropyl distarch phosphate. Claim 8 A hygroscopic composition according to claim 1, wherein the composition ratio of the modified starch to the starch is 9:1 to 1:9 by weight. Claim 9 A hygroscopic composition according to claim 1, wherein the hygroscopic composition further comprises an additive. Claim 10 In claim 1, the above-mentioned desiccant composition is a desiccant composition having a moisture absorption rate of 150% or more at 50°C and 95% relative humidity. Claim 11 In claim 1, the above-mentioned desiccant composition has a moisture absorption rate of 2% / 2hr or more at 50℃ and 95% relative humidity. Claim 12 In claim 1, the desiccant composition is a desiccant composition having a percentage of the amount of moisture absorbed for 14 days at 50°C and 30% relative humidity at 24 hours (hr) of 60% or less. Claim 13 A moisture absorbent pack comprising a moisture absorbent composition selected from any one of claims 1, 3, 5 and 7 to 12 and a packaging material for a moisture absorbent containing said moisture absorbent composition. Claim 14 In claim 13, the packaging material for the desiccant comprises a polyester nonwoven fabric layer, a polyolefin breathable layer, and a polyolefin-based perforated film layer, wherein each layer further comprises a polyurethane-based adhesive layer, and the polyolefin-based perforated film has a plurality of perforations, the gley permeability of the packaging material for the desiccant is 100 to 3,000 seconds, and the moisture permeability of the packaging material for the desiccant is 500 to 5,000 g / m²·24hrs, the absorbent pack has an absorption rate of 300 to 320% at 50°C and 95% relative humidity, the absorbent pack has an absorption rate of 5 to 7% / 2hr at 50°C and 95% relative humidity, and the absorbent pack has an absorption amount at 80°C and 95% relative humidity for 14 days at 50°C and 95% relative humidity 30%, percentage of release at 30% or less in 24 hours, moisture pack. Claim 15 In claim 14, the polyolefin-based perforated film has 1 to 500 pieces / cm 2 An absorbent pack that is a polyolefin-based perforated film having perforations formed therein. Claim 16 In claim 14, the above-mentioned polyurethane adhesive is a polyurethane adhesive derived from a polyester-based polyol and a polyether-based polyol, in a moisture-absorbing pack. Claim 17 delete Claim 18 delete Claim 19 delete
Citation Information
Patent Citations
High performance desiccant with excellent durability and stability
KR1020210042839A
Desiccant composition and desiccant product comprising the same
KR1020210152080A
A composition for moisture absorbent and desiccant for industrial having thereof
KR102265964B1
Packaging material for desiccant and moisture absorption product containing same
KR102413342B1